PEMINGGIRAN MINORITAS DAN ABSENNYA MULTIKULTURALISME DI RANAH LOKAL (STUDI KASUS KOMUNITAS MUSLIM SYIAH DI SAMPANG) - Wahyudi, Johan; Wahid, Makmun (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2015)
This paper tries to explain the practice of marginalization of minority groups and the absence of multiculturalism in Sampang. The preference of the government of Sampang to relocate Shi’i’s Muslim community in the context of conflict resolution, can be read as an attempt to exclude minorities. At the same time, multiculturalism ignored when policy options are taken only for the sake of electoral moment. Therefore, at the end of discussion, this paper emphasizes the need for improvement of the boarding school education system and revitalizing the role of ulama’ to keep multiculturalism and prevent acts of violence against minorities.